Familial clustering and presenceof maternal influence on the transmission of type 2 diabetes in South Indians - Lalitha R; Anil Kumar R; Surekha B Shetty (International Journal of Medical Research and Review, 2018)
Type 2 diabetes mellitus (T2D) is a chronic metabolic disorder, characterized by hyper glycaemia caused by impaired glucose homeostasis and represents a serious public health problem. T2D is a multi-factorial disorder depending on complex interactions between environmental factors and genetic variants.Objective: To evaluate the degree of familial aggregation and maternal influence on the transmission of type 2 diabetes in the South Indian population.Methodology: A total of 1063 subjects with type2 diabetes with knowledge of history of presence or absence of diabetes in relatives were randomly recruited. 652 were male and 411 were female.Results: This study showed familial clustering and maternal transmission in our study population. 78.3% of the subjects had at least one relative with diabetes. Familial aggregation was significant with presence of diabetes in 1st degree relative like parents and in siblings. 2nd degree relatives too had significantly associated with diabetes to a similar extent like 1st degree relatives.Patient’s age range between 50-59 showed highest incidence of diabetes at 44% followed by 37% in age group 40-49. Our study showed an advancement of incidence of diabetes by one decade compared to similar studies in different regions.Conclusion: Maternal factors do play an important role in the incidence of diabetes, prevalence of diabetes. Several factors may be involved in this in terms of polycystic ovaries, gestational diabetes, malnourishment during pregnancy, and other socioeconomic factors. We need studies and further research in ascertaining the exact mechanisms. Familial aggregation is common and may help us to screen for diabetes in high risk populations. Preventive strategies for type 2 diabetes should be directed at these high risk groups.